A STRUGGLE FOR HAPPINESS IN F. SCOTT FITZGERALD'S THE GREAT GATSBY: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - RINI, RESTU WIDIYA (2007)
This study is aimed to investigate how struggle for happiness is reflected in F. Scott Fitzgerald's The Great Gatsby viewed from individual psychological approach. Besides, this study is also aimed to examine the structural elements of the novel. In this study, the writer employs qualitative study in which there are two data sources in this method, namely primary and secondary data sources. The primary data sources and the object of the study is the novel it self. While the secondary data sources are biography of the author, and other relevant information. The writer collects the data from both primary and secondary data sources in sort of a document as evidence. Based on the analysis, the writer draws some conclusions as follow: first, The Great Gatsby is F. Scott Fitzgerald's literary work that tells us about the struggle for happiness of one of major characters, namely Jay Gatsby. Second, Jay Gatsby's psychological problem may represent the psychological case that the author derives from his experiences or observation. The last, the struggle for happiness can influence one's life and the others. It is reflected by one of major characters that do the influence for other people.